Customer value co-creation behavior: Scale development and validation - Yi, Youjae; Gong, Taeshik (Journal of business research, 2013)
This investigation reports a series of four studies leading to the development and validation of a customer value co-creation behavior scale. The scale comprises two dimensions: customer participation behavior and customer citizenship behavior, with each dimension having four components. The elements of customer participation behavior include information seeking, information sharing, responsible behavior, and personal interaction, whereas the aspects of customer citizenship behavior are feedback, advocacy, helping, and tolerance. The scale is multidimensional and hierarchical, and it exhibits internal consistency reliability, construct validity, and nomological validity. This study also shows that customer participation behavior and customer citizenship behavior exhibit different patterns of antecedents and consequences.